Penanganan Longsor dan Rencana Anggaran Biaya dengan Bronjong di Dusun Samondung Kecamatan Lenteng Sumenep - Firatama, Aditya Dandy; Putra, Efendi Pratama; Ishaq, Ishaq; Wardi, Ahmad Helmi Zaki; Hisam, Moh. Abqariyyin (Universitas Muhammadiyah Palembang, 2025)
The river in Samondung Hamlet, Lenteng Subdistrict, Sumenep District is one of the rivers that often occurs landslides on the cliffs. It occurs because of the erosion of water against the river cliff, resulting in damage and causing landslides. Determining the gabion dimensions and Budget Plan Cost (RAB) in Samondung Hamlet Lenteng District Sumenep was the aim of this study. SNI 03-0090-1999 is used in the gabion dimension planning method, and the AHSP Sumenep District in 2024 is used to calculate the Budget Plan Cost (RAB) in this study. The study's findings revealed a dimensional plan of gabions used in the river in Samondung hamlet Lenteng District Sumenep Regency. These gabions are type D, measuring 2 x 1 x 0,5, with a capacity of 1 m³, holes measuring 80 mm by 100 mm, three windings, tensile strength of 41 kg/m², and a weight of 15,5 kg per sheet. Budget Plan Cost (RAB) of cliff reinforcement design from STA 0+000 to STA 0+150 amounted to Rp. 92.332.226,00 inc. PPN 11%.